First insight on ethnobotanical appraisal of plants used traditionally as medicine by Berber community (Amazigh-speaking), living in Driouch province (North eastern Morocco) - Ajjoun, Mohammed; Fakchich, Jamila; Elachouri, Mostafa (Ethnobotany Research and Applications, 2021)
Background: Most ethnobotanical studies carried out in different regions of Morocco revolved around documentation of medicinal plants and their medical uses. However, little is known about ethnobotanical knowledge coupled to Berber community living in “Driouch province” (Northeastern region of Morocco). This study aimed to identify and document medicinal plants used traditionally by local people to manage health problems while investigating and comparing ethnobotanical patterns obtained in this region with other findings reported elsewhere. Methods: Ethnobotanical surveys were carried out between January 2017 and August 2019 in several regions within Driouch province. Ethnobotanical data were collected using standard methods and with prior informed consent. Quantitative analyses were performed by using some indexes and formulas, including Use Value (UV), Family Use Value (FUV), Informant Consensus Factor (ICF) and Jaccard Index (JI). Results: A total of 997 local inhabitants (415 male and 582 female) were interviewed. The plants listed (158) were reflected by a high number of families (60) and genera (137). Regarding the number of species/Family, Lamiaceae was the leading family with 15 species. Among diseases treated, respiratory diseases were ranked first with a rate of 26.46%. The high ICF (0.97) was calculated for respiratory diseases and the most important medicinal plant recorded were Origanum compactum Benth with UV=0.55. Conclusions: The present study revealed that the people living in Driouch province holds significant knowledge about medicinal plant resources. Despite the development of medical technology, local people still rely on using these herbs for healthcare. Keywords: Ethnobotanical, Medicinal plants, Driouch province, Morocco.